Euglycaemic ketoacidosis in pregnant women with COVID-19: two case reports - Margaret Pikovsky; Min Yi Tan; Amanda Ahmed; Lynne Sykes; Rochan Agha-Jaffar; Christina K. H. Yu (BMC, 2021)
Abstract Background Euglycaemic ketoacidosis (EKA) is an infrequent but serious condition which usually follows a period of starvation, severe vomiting or illness in individuals with or without diabetes. Ketoacidosis is associated with materno-fetal morbidity and mortality necessitating prompt diagnosis and management. Physiological increases in insulin resistance render pregnancy a diabetogenic state with increased susceptibility to ketosis. COVID-19 is associated with worse clinical outcomes in patients with diabetes and is an independent risk factor for ketoacidosis in normoglycaemic individuals. Case presentations We describe two cases of SARS-CoV-2 positive pregnant women presenting with normoglycaemic metabolic ketoacidosis. Both cases were associated with maternal and fetal compromise, requiring aggressive fluid and insulin resuscitation and early delivery. Conclusion We discuss possible physiology and propose a management strategy for euglycaemic ketoacidosis in pregnancy.